Neglected tropical diseases: recent trends and challenges associated with its rapid diagnosis and effective therapeutic strategies - Kumar, Subrat; Alghamdi, Abdullah; Singh, Puneet Kumar; Pal, Nirmalya; Pattnaik, Ritesh; Alissa, Mohammed; Alghamdi, Suad A.; Abusalim, Ghadah S.; Subhadra, Subhra (Frontiers in Pharmacology, 2026)
Neglected tropical diseases (NTDs) are a distinct group of illness that are primarily prevailing in the tropical regions. NTDs are caused by diverse pathogens including viruses, bacteria, parasites, fungi and toxins, resulting in adverse health, social and economic outcomes. Currently, more than one billion people globally are affected with NTDs, therefore, precise and rapid diagnostic mechanisms are integral for detection and control of NTDs. However, the NTDs programs are underinvested in the progression and enhancement of diagnostic tools. Due to this reason, WHO has released a new road map for NTD 2021–2030 and has pinpointed diagnostics as one of the precedence areas that require concrete action. In order to achieve the 2030 targets, WHO has also established Diagnostic Technical Advisory Group (DTAG) which will help in initiating collaboration among nations to drive advancement in this area. In this review, we explored the epidemiology and burden of NTDs, the challenges in their mitigation, and the available therapeutic interventions for managing these diseases. We have also highlighted the need to holistic approach like “One health” for an effective elimination of NTDs in affected areas. Elimination of NTDs will enhance the socioeconomic levels of the affected regions, thereby assisting in the accomplishment of few sustainable development goals. Thus, there is a need for worldwide commitment for funding to develop fast and safe therapeutic and diagnostic strategies for NTDs.